2021
DOI: 10.7717/peerj.10213
|View full text |Cite
|
Sign up to set email alerts
|

The influence of estrogen deficiency on the structural and mechanical properties of rat cortical bone

Abstract: Background Post-menopausal osteoporosis is a common health problem worldwide, most commonly caused by estrogen deficiency. Most of the information regarding the skeletal effects of this disease relates to trabecular bone, while cortical bone is less studied. The purpose of this study was to evaluate the influence of estrogen deficiency on the structure and mechanical properties of cortical bone. Methods Eight ovariectomized (OVH) and eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“… 86 In particular, an increase in the mechanical strength of cortical bone was observed in ovariectomized rats with AAS use, a finding that led to the development of AAS as a potential lead for treating established osteoporosis associated with aging. 87 AAS has shown stimulation of endosteal bone formation. These findings have provided recommendations for AAS use particularly ND and nandrolone in estrogen-deficient conditions.…”
Section: Effects On Bonesmentioning
confidence: 99%
“… 86 In particular, an increase in the mechanical strength of cortical bone was observed in ovariectomized rats with AAS use, a finding that led to the development of AAS as a potential lead for treating established osteoporosis associated with aging. 87 AAS has shown stimulation of endosteal bone formation. These findings have provided recommendations for AAS use particularly ND and nandrolone in estrogen-deficient conditions.…”
Section: Effects On Bonesmentioning
confidence: 99%
“…It is a highly optimized bone structure with unified structure and function. Shipov et al [ 18 ] found that elastic modulus in the cortical bone of OP group was less than normal group. Previous studies reported that changes in bone micro—structure is associated with the bone strength [ 19 ].…”
Section: Introductionmentioning
confidence: 99%